Dari Konsumsi ke Adaptasi: Media Sosial Bagi Pelaku Usaha Warung Madura di Era Digital - Nadya Poernamasari; Dinara Maya Julijanti (CV. ITTC INDONESIA, 2026)
Social media reports and discussions about restrictions on 24-hour Warung Madura operations have prompted varied responses from business owners. This study uses the concepts of new media, User Generated Content (UGC), and media literacy to examine trends in reporting and social media use. The focus is on creative economy entrepreneurs, especially those operating Warung Madura businesses. The research uses a mixed-methods approach. It includes interviews and questionnaires distributed to 80 respondents from Bangkalan, Sampang, Pamekasan, and Sumenep in Madura Island. A key trend is business owners' strong reliance on their devices. This is supported by the finding that 57.50% of these entrepreneurs are from Generation Z. Their media use leans toward audiovisual content, with 66.25% favoring TikTok. Notably, 40% of Warung Madura owners spend over 5 hours daily on social media to gather information. This shows that these entrepreneurs are adapting to current times and technology. Media access helps information move more easily through all their business activities.